Measuring emotional intelligence in adolescents: validation data on some new ability-based tests - Buško, Vesna (Array, 2011)
The study presents a part of validation procedures pertaining to the new performance measures designed to assess aspects of emotional intelligence ability in early adolescence age. The instruments were created following Mayer and Salovey (1997) four branches conception of EI, and include a composite measure of emotional management ability (Babić & Buško, 2010) and an adapted version of Emotional analysis test (Kulenović et al., 2000) intended to measure understanding and analysis of emotions. Besides, the test of Perception of affective content in art (Takšić et al., 2004), designed to assess perception of emotions was also administered as well as two short measures of self-esteem and empathy. The data stem from two independent samples of students of higher grades of elementary school in Đakovo, Croatia, with follow-up data collected on one of the samples. The evidence of convergent and discriminant validity of the EI instruments will be presented along with reliability analyses of the instruments which were performed within the context of both classical test theory and the latent state-trait theory (Steyer et al., 1992). Measurement invariance of the scale as a function of age and gender was tested via confirmatory factor procedures.